Comparison of Remove-Compute-Restore and University of New Brunswick Techniques to Geoid Determination over Australia, and Inclusion of Wiener-Type Filters in Reference Field Contribution - Featherstone, Will; Holmes, S.; Kirby, Jon; Kuhn, Michael (ASCE, 2004)
The commonly adopted remove-compute-restore (RCR) technique for regional gravimetric geoid determination uses the maximum degree of a combined global geopotential model and regional gravity data via the spherical Stokes integral. The University of New Brunswick's (UNB) technique involves the use of a deterministically modified integration kernel, a degree-20 satellite-only reference field, integration of high-frequency terrestrial gravity anomalies over a spherical cap of 6 radius about each computation point, and a separate computation of the truncation bias used Degrees 21 120 of a combined global geopotential model. Both approaches are tested over Australia and the resulting geoid models compared with a nationwide dataset of 1,013 Global Positioning System (GPS)-leveled points, and with the most recent Australian geoid model, AUSGeoid98. A subsequent experiment considers the commission errors in the reference field used by applying a Wiener-type filter based on the global degree- and error-degree variances of the EGM96 combined and EGM96S satellite-only global geopotential models. The theoretical basis of this adapted approach will be presented, together with comparisons of the resulting geoid solution with the 1,013 GPS-leveling data, UNB, RCR, and AUSGeoid98 solutions.